Management of early-stage gastro-esophageal cancers: expert perspectives from the Australasian Gastrointestinal Trials Group (AGITG) with invited international faculty. Issue 4 (2nd April 2020) - Roy, Amitesh C.; Shapiro, Jeremy; Burge, Matt; Karapetis, Christos S.; Pavlakis, Nick; Segelov, Eva; Chau, Ian; Lordick, Florian; Chen, Li-Tong; Barbour, Andrew; Tebbutt, Niall; Price, Tim
ABSTRACT: Introduction : A multimodal approach in operable early-stage oesophago-gastric (OG) cancer has evolved in the last decade, leading to improvement in overall outcomes. Areas covered : A review of the published literature and conference abstracts was undertaken on the topic of optimal adjunctive chemotherapy or chemoradiotherapy in early-stage OG cancers. This review article focuses on the current evidence pertaining to neoadjuvant and perioperative strategies in curable OG cancers including the evolving landscape of immunotherapy and targeted drugs in this setting. Expert commentary : Adjunctive therapies in the form of preoperative chemo-radiotherapy (CRT) or chemotherapy and perioperative chemotherapy over surgery alone improve outcomes in patients with operable OG cancer. Although there are variations in practice around the world, a multi-disciplinary approach to patient care is of paramount importance. Immunotherapy and on treatment functional imaging are two examples of emerging strategies to improve the outcome for early-stage patients. A better understanding of the molecular biology of this disease may help overcome the problem of tumor heterogeneity and enable more rationally designed and targeted therapeutic interventions in the future.